Effects of Ospemifene on Breast Tissue Morphology and Proliferation: A Comparative Study Versus Other Selective Estrogen Receptor Modulators in Ovariectomized Rats - Kangas, L.; Härkönen, P.; Väänänen, K.; Keskitalo, J.; Eigéliené, N. (Hormone and Metabolic Research, 2014)
Ospemifene is a tissue-selective estrogen agonist/antagonist that was recently approved for the treatment of dyspareunia associated with vulvar and vaginal atrophy, which occurs in up to approximately 50% of postmenopausal women. The current analyses were conducted to determine whether ospemifene exhibits estrogenic activity in the mammary glands of ovariectomized rats and to compare potential estrogenic activity with selective estrogen receptor modulators (tamoxifen, raloxifene, and toremifene). Three separate studies with differing durations (6, 9, and 28 days) were conducted using similar procedures in ovariectomized Sprague-Dawley rats. Estradiol treatment and sham-treated ovariectomized rats were used as positive and negative controls, respectively. Cell proliferation was examined using labeled 5-bromo-2-deoxyuridine; cytoplasmic prolactin was characterized with antibody staining. The morphology of the mammary gland was studied by histological staining of sections from the right fourth mammary glands, and the excised gland from the left side was used for counting the lobulus number. Neither ospemifene nor selective estrogen receptor modulators substantially induced 5-bromo-2-deoxyuridine staining, altered the morphology of the mammary glands, or changed prolactin immunostaining in ovariectomized rats compared with the ovariectomized controls. With the exception of toremifene, the selective estrogen receptor modulators did not cause a substantial induction in mammary gland lobuli. Estradiol had effects opposite to those of the selective estrogen receptor modulators in these studies. Ospemifene exhibited no substantial estrogenic activity in the mammary gland of ovariectomized rats. Activity in the mammary gland of ovariectomized rats with ospemifene was comparable to raloxifene and tamoxifen.
Keywords: ospemifene; selective estrogen receptor modulator; antiestrogenic effects; mammary gland; breast